Comparative Evaluation of Antibacterial Effect of Propolis and Aloe Vera, Xylitol, and Cpp-Acp Gels on Streptococcus mutans and Lactobacillus in Vitro - Maryam Hajiahmadi; Jamshid Faghri; Zohre Salehi; Fariba Heidari (International Journal of Dentistry)
Introduction. Early childhood caries is a kind of caries occurring in deciduous teeth. Bacteria are among the main factors. Antibacterial agents such as fluoride are used in both prevention and treatment, but their application in children faces limitations such as fluorosis. Therefore, novel methods of caries prevention among the children are mainly focused on the use of fluoride-free active ingredients. In this comparative study, antibacterial effects of gels containing propolis and aloe vera, fluoride, xylitol, and CPP-ACP were investigated. Methods. This is an in vitro study. By plate well technique, plates containing gels were created in the culture medium of Streptococcus mutans and Lactobacillus, and their antibacterial impacts were evaluated by measuring the inhibition zone after 24, 48, and 72 hours. Then, different concentrations of each gel were evaluated in the same way for the antibacterial properties. For each sample, this process was iterated 3 times, where the average was declared as the final number. The collected data were entered in SPSS 24. Results. In both bacteria, propolis gel and aloe vera had the highest zone of inhibition, followed by fluoride and xylitol in the second and third places, respectively. Different concentrations of gels are significantly different in terms of antimicrobial effect (P value ≤ 0/05). The antimicrobial effect of propolis and aloe vera gel was kept up to the concentration of 1/16. As the bacterial and gel contact time is prolonged, the antibacterial effect of different gels increases, but the difference is not statistically significant (P value = 0.109). CPP-ACP gel had no antimicrobial effect at any concentration. Conclusion. Propolis and aloe vera gel had a greater antimicrobial effect than other gels, where such effect was observed in low concentrations. CPP-ACP gel had no antimicrobial properties.